End stage renal failure: 14 years' experience of dialysis and renal transplantation. Issue 2 (February 1988) - Offner, G; Aschendorff, C; Hoyer, P F; Krohn, H P; Ehrich, J H; Pichlmayr, R; Brodehl, J
Abstract : One hundred and thirteen children (59 boys and 54 girls aged from 2 to 16 years) with end stage renal failure entered the renal dialysis and transplantation programme between 1972 and 1983. They were followed up until December 1985. Ninety eight children were initially treated by haemodialysis in hospital and 15 by renal transplantation. The average wait on dialysis was seven months (range 0.1-43 months). One hundred and six children were given 129 renal transplants, 32 of which were from living related donors. At the end of 1985 94 of the 113 patients (83%) were alive, 81 (72%) with functioning grafts, 11 (10%) were receiving haemodialysis in hospital, two (1%) were being treated by continuous ambulatory peritoneal dialysis, and three had been lost to follow up. The 14 years actuarial survival was 81%. Four patients receiving dialysis and 12 who had received transplants died, a mortality of 14%. The main complications of treatment were retardation of growth in 49 (43%), hypertension in 75 (66%), and osteopathy in 36 (32%). Retardation of growth could not be reversed by successful renal transplantation. Seventy two patients (88%) assessed their health as good to excellent, and 9 (12%) as poor. Patients with a functioning graft did much better than those receiving dialysis. Treatment of end stage renal failure led to full rehabilitation in most patients, and renal transplantation was more effective than dialysis.